TINJAUAN KOMPREHENSIF PROGRAM PENDIDIKAN AKHLAK MENGGUNAKAN KERANGKA KERJA CIPP: STUDI KASUS MI TAMRINUSSIBYAN 01 AL HIKMAH - Atqia, Qy; Marliana Susianti, Oni (Institut Daarul Qur'an Jakarta, Indonesia, 2025)
Moral education manifested in real behavior through role models. This study aims to evaluate the moral education program at MI Tamrinussibyan 01 Al-Hikmah with a focus on the planning, implementation, and results of the program. This study used a qualitative approach with subjects including the principal, sixth grade teachers, parents, and sixth grade students. Data collection techniques were carried out through interviews, observation, and documentation. The results of the study indicate that: (1) in the planning aspect, the human resources component and the availability of infrastructure still require quality improvement; (2) in the implementation aspect, the moral education program has been optimally integrated into all learning activities and school culture; (3) in the outcome aspect, the achievement of religious attitudes, honesty, and politeness of students has been in accordance with educational objectives, but the attitude of responsibility and love for the environment still requires further development. Based on the evaluation results, it is concluded that strategic improvement efforts are needed in the planning dimension and strengthening the output of results in order to achieve the objectives of comprehensive moral education.